ПРОГРАМИ СОЦІАЛЬНО-ЕКОНОМІЧНОГО ТА КУЛЬТУРНОГО РОЗВИТКУ РЕГІОНУ ЯК ІНСТРУМЕНТ РЕАЛІЗАЦІЇ ДЕРЖАВНОЇ РЕГІОНАЛЬНОЇ ПОЛІТИКИ - Кроленко, Дмитро Юрійович (SUPREMANCE OF LAW, 2017)
The article deals with the basic principles of the state regional policy, regional social-economic development programs are determined as one of the leading tools of implementation of the state regional policy, order of development programs of regional councils are characterized, the structure, main principles and objectives and mechanisms for implementation and monitoring of programs are characterized.